Development of Novel Solar Cell Design based on Current Energy Converted from Phonon Energy by Controlling the Phonon Transport - Tin Swe, Hsu Myat; Hla Myo Tun; Pradhan, Devasis; Win, Lei Lei Yin; Khin, Ei Ei; Soe, Khaing Thandar (Journal of Novel Engineering Science and Technology, 2024)
The paper mainly focuses on the Development of Novel Solar Cell Design based on Current Energy Converted from Phonon Energy by Controlling the Phonon Transport. The research challenges in this study are: to find a means of the control of phonon transport or phonon accumulation and propose a novel solar cell structure to convert the phonon energy to the current energy; to study phonon control method for III-nitrides and the properties of phonon transport; to analyze the phonon absorption in a short time for III-nitrides is higher than gallium arsenide by one order, which makes it possible to extract higher current than previous materials. The research objectives are: to design the novel solar cell structure to convert Phonon Energy to Current Energy; to analyze the physics of solar cell structure with numerical approaches; to model the Quantum Well in the proposed solar cell structure; to set the experimental measurement system for physical characteristics of novel solar cells; to confirm the results from the analysis of Control of Phonon Transport. The conversion of current energy from the phonon energy by controlling the phonon transport depends on the structure of the solar cell stacking system. The implementation of this study was accomplished based on the specific model, especially Quantum Well Structure. The results confirm that the performance specification of targeted solar cell structures in real-world applications.